Psalms as a Vehicle for Historiography - Adamo, David T. (Studia Historiae Ecclesiasticae, 2019)
The Book of Psalms is the most read books of the Bible and one of the most read books in the world. It is also one of the most debatable books of the Bible. The value placed on the Bible as a historical source is fundamentally important. While the maximalists think that the biblical account should be the primary source of the history of ancient Israel, and everything that could not be proved wrong must be accepted as historical, the minimalists think otherwise and rely on the primacy of archaeology because they think that the Bible is not a reliable document in terms of historical account. The centrists acknowledge the value of the biblical texts in preserving reliable evidence on the history of ancient Israel. However, they consider the way the stories were written and presented as highly ideological and believe they were adapted to the needs of the community when they were written. The major contention in this paper is whether the Book of Psalms contains any authentic historical documents/historiography or not. This article maintains that the Bible, particularly the Book of Psalms, contains some reliable historical documents that could be considered as a source of historiography. The Book of Psalms represents the history of ancient Israel in its historical allusions and the praises. This representation of history is, for the writers and readers of the Psalms-whether in chanting, memorising, singing, writing or copying-a way to remember the mighty act of Yahweh and also to participate mysteriously in the actual events that took place in the past history of ancient Israel; so that the present participants can experience the very miracles that took place long ago. It is expected that those miracles and events are able to take place again in the life of the believers who read, write, chant, sing or recount the Psalms.
free